Isolation of bacteria from normal external auditory canal - Prasanna, Vincent; Edwin, Beulah; Kannan, I (International Journal of Medical Research and Review, 2015)
Introduction: Otits Externa is one of the commonest condition with which patients attend the ENT clinics throughout the world. Like the skin, the external auditory canal has the possibility of harboring normal bacterial flora. There is no proper literature regarding the normal bacterial flora of external auditory canal. Thus the clinicians are posed with the difficulty in interpreting the laboratory diagnostic report. Aim of the Study: The aim of the present study is to assess the aerobic bacterial flora of the healthy human ear canal. Materials and Methods: 100 individuals were selected for the study. The sample was collected in the form of ear swabs. The swabs were subjected to culture initially in BHI broth followed by Blood agar and MacConkey agar. The organisms grown were identified by standard biochemical reactions. Results: The present study showed that the S. epidermidis is the commonest bacteria isolated (94%) followed by other bacteria viz., S. aureus, E. coli, P. aeroginosa and diphtheroids. Conclusion: The present study concludes that certain pathogenic bacteria which can cause otitis externa are present as normal commensals in the external auditory canal. Hence the clinicians should elicit the history of any predisposing factors before interpreting laboratory culture reports.